2015
DOI: 10.2807/1560-7917.es2015.20.24.21158
|View full text |Cite
|
Sign up to set email alerts
|

Imported case of MERS-CoV infection identified in China, May 2015: detection and lesson learned

Abstract: At the end of May 2015, an imported case of Middle East respiratory syndrome coronavirus (MERS-CoV) infection was confirmed in China. The patient is in a stable condition and is still undergoing treatment. In this report, we summarise the preliminary findings for this imported case and the results of contact tracing. We identified 78 close contacts and after 14 days of monitoring and isolation, none of the contacts presented symptoms and all tested negative for MERS-CoV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…We report a case of MERS in a 43-year-old man from South Korea who acquired this disease during this outbreak (Technical Appendix Figure 1) ( 4 ). …”
mentioning
confidence: 99%
“…We report a case of MERS in a 43-year-old man from South Korea who acquired this disease during this outbreak (Technical Appendix Figure 1) ( 4 ). …”
mentioning
confidence: 99%
“…Follow-up and laboratory testing indicated that no virus transmission occurred among contacts. Because of the timely notification from South Korea and the World Health Organization regarding the MERS-CoV outbreak ( 4 ), our hospital was able to prepare in advance for admission of the case-patient. No HCWs were infected.…”
Section: Discussionmentioning
confidence: 99%
“…An additional set of specimens was collected from the 3 symptomatic contacts immediately after onset of symptoms. All specimens were tested by real-time reverse transcription PCR, as previously described ( 4 ). No specimens tested positive for MERS-CoV, and follow-up for contacts ended on June 10, 2015.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The disease which is believed to be confined in a region can emerge in new remote setting without prior notification. The existed Chinese case brought several attentions to the local Chinese Centers for Disease Control for implementing a strong disease control measure to stop the progression of the outbreak to the Chinese mainland[14][15][16][17][18][19][20]. The global public health has to continuously follow up the situation and have collabora te to stop the possible worldwide pandemic.…”
mentioning
confidence: 99%